1998
DOI: 10.1172/jci2299
|View full text |Cite
|
Sign up to set email alerts
|

Late blockade of T cell costimulation interrupts progression of experimental chronic allograft rejection.

Abstract: Early blockade of T cell-costimulatory activation pathways prevents development of experimental chronic allograft rejection. Ongoing T cell recognition of alloantigen and activation may also play an important role in progression of chronic rejection, but definitive evidence is lacking. We Our data are the first to demonstrate that blocking T cell-costimulatory activation late after transplantation, after initial graft injury, prevents progression of chronic allograft rejection supporting the hypothesis that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 53 publications
3
65
2
Order By: Relevance
“…Th1 and Th2 cytokines exert a mutual cross-regulation on the precursors of Th1-or Th2-type effector cells which are important mediators in directing the immune system towards the appropriate response. The selective activation of either Th1 or Th2 type cells depends on the antigen and is influenced by cytokines produced partly by antigenpresenting cells and partly by T helper cells (8). Both Th1 and Th2 cytokines are possibly susceptible to the herb activation or suppression (9).…”
Section: Effects On Cytokine Production and Other Immune Effector Cellsmentioning
confidence: 99%
“…Th1 and Th2 cytokines exert a mutual cross-regulation on the precursors of Th1-or Th2-type effector cells which are important mediators in directing the immune system towards the appropriate response. The selective activation of either Th1 or Th2 type cells depends on the antigen and is influenced by cytokines produced partly by antigenpresenting cells and partly by T helper cells (8). Both Th1 and Th2 cytokines are possibly susceptible to the herb activation or suppression (9).…”
Section: Effects On Cytokine Production and Other Immune Effector Cellsmentioning
confidence: 99%
“…In several models, CD28-B7 blockade alone or in combination with donor-specific transfusion (DST), 3 has been shown to prevent acute rejection, induce longterm allograft survival (1)(2)(3)(4), and prevent the development and progression of chronic rejection (5,6). However, the same degree of efficacy is not seen when more stringent transplantation models have been used (7)(8)(9)(10).…”
Section: T Is Now Firmly Established That Costimulatory Signals Prmentioning
confidence: 99%
“…In vitro studies have demonstrated that CTLA4Ig-mediated blocking of CD80/86 results in the development of anergic T cells (16)(17)(18). In addition, the efficacy of CTLA-4Ig in prolonging allograft acceptance in rodent transplantation models suggests that abatacept treatment could promote T cell tolerance.…”
mentioning
confidence: 99%